Trust in decentralized anonymous marketplaces - Zindros, Dionysios (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών, 2015)
This work introduces a decentralized anonymous marketplace. We study the nature of such marketplaces, and we present our implementation of a practical such marketplace which we call OpenBazaar. We then focus our study on the security and trust aspect of such a marketplace. We explore the security implications of decentralization and anonymity, and propose several mechanisms to achieve trust. Our proposals include traditional secure software development mechanisms, which we have applied in practice in our implementation. We also propose the use of an anonymity-preserving transport layer. More importantly, we explore how cryptocurrency mechanisms can be used to achieve trust without the need of central third parties, through the particular mechanisms of arbitration, multisigs, and mutually assured destruction. The cryptographic and game theoretic properties of such schemes are explored, and an implementation using bitcoin is studied. We also propose novel attacks on these schemes. Our contribution includes several mechanisms of achieving trust. We introduce a new form of web-of-trust in which multiplicative rules are used for trust transitivity, while decentralization, security, and anonymity are preserved. We explore the anonymity and security properties of such webs-of-trust and discuss separation attacks. Our contribution also includes the use of proof-of-burn mechanisms to build identities, for which we provide an implementation. Finally, we also contribute with anonymous decentralized naming of stores, for which we also provide an implementation using Namecoin.